The Relations of Parental Autonomy Support, Parental Control, and Filial Piety to Chinese Adolescents’ Academic Autonomous Motivation: A Mediation Model - Guo, Mingchun; Wang, Long; Day, Jamin; Chen, Yanhan (Frontiers in Psychology, 2021)
This study attempted to examine the mediating role of filial piety in the relationships between parental autonomy support and control and Chinese adolescents’ academic autonomous motivation. A set of questionnaires were administered to 492 adolescent students at two senior high schools in Fuzhou, China. Confirmatory Factor Analysis and Structural Equation Modelling were employed to analyze the data. The results showed that reciprocal filial piety fully mediated the relationships of parental autonomy support and behavioral control with adolescents’ academic autonomous motivation. Reciprocal filial piety did not significantly mediate the relationship between psychological control and academic autonomous motivation. Comparatively, authoritarian filial piety did not play a significant mediating role in the relationship between the three parenting dimensions and adolescents’ academic autonomous motivation. The findings provide a new perspective for understanding the relationship between parenting behaviors and Chinese adolescents’ academic autonomous motivation.